2014
DOI: 10.3109/03008207.2014.930140
|View full text |Cite
|
Sign up to set email alerts
|

The effects of platelet-rich plasma on the osteogenic induction of bone marrow mesenchymal stem cells

Abstract: Bone marrow mesenchymal stem cells (BMSCs) are multipotent stem cells. Finding methods to improve the osteogenic potential of these cells is a key factor in bone tissue engineering. Platelet-rich plasma (PRP) contains powerful growth factors that produce changes in a variety of cell types. The purpose of this study was to explore the effects of PRP on the osteogenic differentiation of BMSCs in vitro. Rabbit BMSCs were harvested and cultured in vitro in control media or in media enhanced with PRP. BMSCs began t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…These cultured ADSCs also maintained their differentiation potential, and were able to differentiate into adipocytes and osteoblasts… With these phenotypes, obtained ADSCs satisfied the minimal standard depicted by Dominici et al (Dominici et al, 2006). Similar studies have been successful in replacing FBS with PRP in MSC culture conditions, including those from as bone marrow (Amable et al, 2014;Zou et al, 2014), and umbilical cord blood Van Pham and Kim Phan, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…These cultured ADSCs also maintained their differentiation potential, and were able to differentiate into adipocytes and osteoblasts… With these phenotypes, obtained ADSCs satisfied the minimal standard depicted by Dominici et al (Dominici et al, 2006). Similar studies have been successful in replacing FBS with PRP in MSC culture conditions, including those from as bone marrow (Amable et al, 2014;Zou et al, 2014), and umbilical cord blood Van Pham and Kim Phan, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…Since we have no data regarding activated platelets (P-selectin-positive platelets), the exact influence of active platelets on the circulating CD34-positive cells is unknown. However, a previous study reported that platelet rich plasma enhances the proliferation of bone marrow multi-potent stem cells [6]. Therefore, we believe that the number of platelets correlates with the number of active platelets.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, plasma levels of S1P have been shown to lead to the trafficking of stem cells from the bone marrow to the peripheral blood [5]. Platelets are a rich source of VEGF, SDF-1α, and S1P [3], and platelet-rich plasma could enhance the proliferation of bone marrow mesenchymal stem cells, which are known to be multi-potent stem cells [6]. On the other hand, stem cells are also known to differentiate into megakaryocytes and to subsequently produce platelets [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, BMSCs in bone marrow are rare, with only one BMSC detected in 1 × 10 5 bone marrow mononuclear cells. PRP, as a storage vehicle for growth factors such as PDGF, TGF-β, PDEGF, VEGF, and platelet factor-4, enhances osteogenic differentiation of BMSCs [15]. Many studies have shown that factors that positively affect bone formation and fracture healing also positively affect tendon–bone healing [16].…”
Section: Introductionmentioning
confidence: 99%